Lemierre Syndrome. Issue 1 (4th May 2022) - Boyer, Axel; Médart, Laurent; Collignon, Laurent
Teaching Point: Lemierre syndrome is a rare complication of bacterial pharyngitis with cervical thrombophlebitis leading to pulmonary abcesses; the radiologist may have a key role.